Effects of lysolecithin on growth performance, nutrient digestibility and liver lipid metabolism of yellow-feather broilers - Shuhan Xiang; Mei Zhao; Zheng Li; He Zheng; Yanan Ding; Fang Peng; Jian Xiao; Kun Xie; Haihan Zhang; Xi He; Zehe Song (Italian Journal of Animal Science)
The present study was conducted to evaluate the effect of lysolecithin supplementation in a low-energy diet on growth performance, nutrient digestibility and liver lipid metabolism of yellow-feather broilers. A total of 900 one-day-old male broilers were randomly divided into five treatment groups with 6 replicates. The dietary treatments were followed as control group (CON, basal diet), low energy group (LE, reduced 0.25 MJ/kg of metabolisable energy than basal diet), and experimental groups supplemented with 500, 750, or 1000 g/T of lysolecithin (LPL500, LPL750, and LPL1000) in LE diet. The results showed that LE treatment significantly increased the feed to gain ratio (F/G) of broilers during the whole period compared to CON group. Compared with the LE group, lysolecithin addition reduced the F/G of broiler over the entire period and significantly increased the digestibility of ether extract on 21 d and the VH/CD ratio of the jejunum and ileum over the whole period. Lysolecithin supplementation also increased chymotrypsin activity on 21 d and lipase activity on 52 d in duodenum and apolipoprotein A4 (APOA4) expression in liver tissue on 52 d compared with LE treatment. In conclusion, lysolecithin could alleviate the growth retardation caused by low ME diet through improving lipase and chymotrypsin activity, intestinal morphology, nutrients digestibility and absorption.